The Effect of Adding Wire Mesh on the Compressive Strength of Concrete Using Peat Water and Sea Water - M.Hanif Faisal; Firmanilah Kamil; Julyan Purnomo (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2026)
Concrete is a widely used construction material due to its strength and durability, but its quality is greatly influenced by its constituent materials and the environment. In West Kalimantan, people use scrap wire from building demolition as an additive in concrete, while clean water is limited, so peat water or seawater is often used as a mixer. This study aims to determine the effect of wire mesh usage and mixing water type on concrete compressive strength at 7, 14, and 28 days. Test specimens in the form of cubes were made with variations: normal concrete (clean water), concrete with peat water, concrete with seawater, and concrete with 1% wire mesh added to each type of water, and compressive strength testing was conducted using a compression testing machine. The results showed that peat-water concrete achieved the highest strength (119.50, 207.37, and 247.73 kg/cm² at 7, 14, and 28 days), seawater concrete produced the lowest (92.87, 182.27, and 225.90 kg/cm²), and the addition of 1% wire mesh increased early-age strength up to 186.57 kg/cm² at 7 days but its effect diminished at later ages. Thus, the type of mixing water plays a dominant role in concrete quality, while steel tie wire is more effective in increasing strength during the early stages of hardening.